Facile CO Cleavage by a Multimetallic CsU2 Nitride Complex. (6th September 2016) - Falcone, Marta; Kefalidis, Christos E.; Scopelliti, Rosario; Maron, Laurent; Mazzanti, Marinella
Abstract: Uranium nitrides are important materials with potential for application as fuels for nuclear power generation, and as highly active catalysts. Molecular nitride compounds could provide important insight into the nature of the uranium–nitride bond, but currently little is known about their reactivity. In this study, we found that a complex containing a nitride bridging two uranium centers and a cesium cation readily cleaved the C≡O bond (one of the strongest bonds in nature) under ambient conditions. The product formed has a [CsU2 (μ‐CN)(μ‐O)] core, thus indicating that the three cations cooperate to cleave CO. Moreover, the addition of MeOTf to the nitride complex led to an exceptional valence disproportionation of the CsU IV –N–U IV core to yield CsU III (OTf) and [MeN=U V ] fragments. The important role of multimetallic cooperativity in both reactions is illustrated by the computed reaction mechanisms.